Brugen af kapelbetegnelsen i det middelalderlige Slesvig Stift: Aspekter af det slesvigske sognemønsters etablering og udvikling - Pedersen, Morten (Hikuin, 2006)
The use of the term capella in the medieval diocese of Slesvig Aspects of the formation and developement of the parochial system By Morten Pedersen In written sources churches in the diocese of Slesvig in the southern parts of medieval Denmark are often termed capella. This is an unique situation compared to the other parts of medieval Denmark where capella does not appear to have been commonly used. In the article the use of capella in the written sources from Slesvig is discussed. It is shown how the term first of all denoted new churches who were not yet in a position as full parish churches. With examples it is shown how their pastoral care was often limited at the expense of the old motherchurches to which they also could be under different kinds of obligations. In the western parts of the diocese, the Wadden Sea, the use of capella seems to spring from a situation where relics of arrangements from the early 13. century comparable to the English ‘old-minsters’ were preserved into the late middle ages. In these remote districts systems with old baptismal churches and smaller and less significant chapels does not seem to have been eradicated by the establishing of the more homogeneous parish structure in the 12. and 13. centuries. But capella were also used for churches who due to floods, wars, plague or other crisis had difficulties scraping along and therefore seems to have been annexed to other parish churches. It is shown how danish churches entered into such arrangements in the early 13. century and not only as a consequence of the crisis in the middle of the 14. century as has been generally assumed by danish historians.